LEGAL PROTECTION FOR COPYRIGHT HOLDERS OF ONLINE GAME SOFTWARE: THE ECONOMIC RIGHTS OF THE CREATOR - Triana Dewi Seroja; Rina Shahriyani Shahrullah; Indra Hengky (UNES Law Review, 2023)
In the game industry itself, particularly in Indonesia, the majority of game developers and publishers are copyright holders who are not the creators themselves, often referred to as license holders. To analyze the legal protection for copyright holders of online game software in relation to the economic rights of the creator, Philipus M. Hadjon's Theory of Legal Protection can be used. The objectives of this research are to analyze the legal regulations for copyright holders of online game software, to analyze the legal protection for copyright holders of online game software in relation to the economic rights of the creator, and to analyze the role of the Government in providing legal protection for copyright holders of online game software. The research used a normative juridical approach, therefore the data used are secondary data obtained from existing literature. It employs qualitative juridical data analysis. The results of the research show that in the legal protection for copyright holders of online game software in relation to the economic rights of the creator, according to Philipus M. Hadjon, "there are two types of legal protection means, namely Preventive Legal Protection means that can be resolved through arbitration/non-litigation, such as Mediation, Negotiation, Conciliation, Arbitration.